(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This research focuses on the development of a Conceptual Model of an automated system for processing information from open sources and detecting information deviations. The purpose of the model is to provide a framework within which to develop and implement technologies and methods that will enable the system to effectively collect, process, and analyze information from a variety of sources. The automated system concept is intended to improve the efficiency and accuracy of intelligence work by using automated methods and algorithms to analyze large volumes of data and information. To achieve this goal, the components and functions of the system will be discussed, as well as the ways in which they interact. The model proposes an integrated approach combining different technologies and methods to achieve efficient information processing and detection of deviations. The proposed system has the potential to be applied not only in the security sector, but also in various fields such as business, finance, medicine, and others where information from open sources is essential for decision making.